Oxidative stress response and virulence factors in Candida glabrata clinical isolates - Berila, N; Hyroššová, P; Subík, J (Folia microbiologica, 2011)
We determined the susceptibility to oxidative stress and assessed the four virulence factors of the 38 Candida glabrata clinical isolates originating from two teaching hospitals in Slovakia. All the isolates were susceptible to hydrogen peroxide, diamide, and 7-chlorotetrazolo[5,1-c]benzo[1,2,4]triazine (CTBT) inducing an increased formation of reactive oxygen species in fungal cells. The mean relative cell surface hydrophobicity (CSH) of isolates was 21.9, ranging from 1.92 to 56.96. All isolates showed biofilm formation. A high biofilm formation was observed among 60.5% of isolates. Positive correlations were observed between biofilm formation and moderate values of CSHs. The 76.3% and 84.2% of isolates displayed varying degrees of proteinase and phospholipase activity, respectively. These results demonstrate a differential distribution of factors contributing to virulence of C. glabrata clinical isolates and point to their significance in pathogenesis that would be targeted by novel antifungals.
Keywords: hydrofobní a hydrofilní interakce; triaziny; Peptide Hydrolases; Diamide; Virulence Factors; oxidancia; proteasy; Candidiasis; reaktivní formy kyslíku; Hospitals, Teaching; Stress, Physiological; diamid; fosfolipasy; biofilmy; peroxid vodíku; Oxidative Stress; fyziologický stres; Triazines; Slovakia; Reactive Oxygen Species; Hydrophobic and Hydrophilic Interactions; Slovenská republika; ženské pohlaví; Biofilms; Humans; Oxidants; Candida glabrata; Phospholipases; nemocnice fakultní; oxidační stres; faktory virulence; Female; kandidóza; Hydrogen Peroxide; lidé